A Framework of Collaborative Virtual Environments for Design Research - Gul, F.; Wang, Xiangyu; Kim, M. (NOVA Science Publishers Inc, 2013)
Recent advances in Collaborative Virtual Environments (CVEs) have attracted noted research efforts in using it for assisting design and facilitating design collaboration. This paper proposes a CVEs framework for design research that focuses on practicability of each variable for providing design assistances in specific projects. Although previous work in CVE is design has properly addressed the variables in an isolated manner, comprehensive issues in terms of CVE effectiveness in design assistance need to be further developed. The comprehensive CVE framework consists of three dimensions and thirteen categories, which further critically reviews each of the variables in its implication of design assistance based on the findings from representative literature. This framework provides a basis for evaluating potential and important research areas and identifying driving factors for future CVE research in design assistance.